Translanguaging in Computer Programming: "¿Qué no es un cereal?" - Ynostroza, Adeli; Celedón-Pattichis, Sylvia; Pattichis, Marios; Tovar, Irán; Ibarra, Melissa (International journal of multicultural education, 2025)
Although there have been efforts to broaden the participation of underrepresented students in Science, Technology, Engineering, and Mathematics (STEM), few studies have focused on how Latine bilingual students in rural contexts can access computer programming. The purpose of this case study is to examine how translanguaging facilitates understanding among emergent bilingual students. The findings showed how translanguaging is more than translation, how students used their linguistic repertoire to negotiate meaning, and the use of language brokering as a pedagogical tool. Implications for translanguaging in STEM have the potential for a deep understanding of computer programming concepts.